Socio-Clinical Profile Of HIV Patients Visiting To An Art Centre (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2014)
Introduction: Scenario of the AIDS epidemic, clinical course and pattern of opportunistic infections in HIV patients is changing world-wide. The study aims to fulfill the paucity of socio-clinical profi le among the patient of HIV with geographical population of this region. Methodology: This is a hospital based cross sectional clinical study with a sample size of 110 respondents presenting to ART center at Jayarogya Hospital (JAH) Gwalior from May 2010 to Oct 2011. Results: Mean age of study population was 35.44±9. High Frequency of weight loss > 10% (P